Organizational exposure to risk of unethical behaviour : in Eastern European timber purchasing organizations - Norberg, Daniel; Gustafsson, Emil (SLU/Dept. of Forest Products, 2008)
Issues: The issues Swedwood asked us to explore in their Eastern European timber purchasing organizations were:  Have clear directives been given to each purchasing unit regarding the purpose and scope of its activities?  If so, what do these directives contain?  If so, how are these directives followed?  How are purchasing transactions planned and carried out?  What roles are involved in the purchasing process, and what are the responsibilities and authorities of each role?  Can the purchasing process, or parts of the process, be improved?  Can the company organize its purchasing units more effectively to ensure best practices?